Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.pcc.0000149138.65083.ef
|View full text |Cite
|
Sign up to set email alerts
|

Low bias flow oscillation with heliox in oleic acid-induced lung injury

Abstract: Helium concentrations greater than 40% increase Co(2) clearance from oleic acid-injured lungs of rabbits during low bias flow oscillation. The low bias flow oscillation system makes this possible using 1% of the gas volume required during high-frequency oscillatory ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
1
4
1
Order By: Relevance
“…Heliox allowed for a reduction in minute volume ventilation, while CO 2 removal remained unaltered. These effects are in line with findings in pediatric ARDS models [12,13,14], as well as in pediatric and adult patients with respiratory failure due to exacerbation of COPD or asthma [9,10,18,19,20]. In ARDS models, heliox has mostly been studied as a driving gas during HFOV.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Heliox allowed for a reduction in minute volume ventilation, while CO 2 removal remained unaltered. These effects are in line with findings in pediatric ARDS models [12,13,14], as well as in pediatric and adult patients with respiratory failure due to exacerbation of COPD or asthma [9,10,18,19,20]. In ARDS models, heliox has mostly been studied as a driving gas during HFOV.…”
Section: Discussionsupporting
confidence: 78%
“…In paediatric animal models of ARDS [12,13,14], heliox ventilation was found to improve gas exchange during high–frequency oscillatory ventilation and attenuate lung inflammation [13]. However, data on the effect of heliox on ARDS during conventional mechanical ventilation are sparse and data are limited to paediatric models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heliox ventilation showed no effect on neither gas exchange or on lung inflammation. Thereby, our results are somewhat in contrast to studies investigating heliox ventilation in pediatric models as well as to findings in our own animal model of ventilator-induced lung injury, where heliox improved CO 2 removal [ 13 17 ].…”
Section: Discussioncontrasting
confidence: 95%
“…The use of heliox has been evaluated in pediatric animal models of ARDS induced by oleic acid or saline [ 13 15 ], showing that heliox ventilation improved gas exchange during high-frequency oscillatory ventilation. We recently showed that heliox improves CO 2 removal and decreases driving pressures in patients who are mechanically ventilated according to the recommended protective strategy, as well as in an animal model of lung injury inflicted by high tidal volume ventilation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an adult rabbit model of ARDS, lung injury was induced by oleic acid instillation [29]. Animals were ventilated with low bias flow oscillation with a CO 2 scrubber, which is a modified HFOV system to reduce gas utilisation.…”
Section: Resultsmentioning
confidence: 99%